Blood coagulation abnormalities and the usefulness of D-dimer level for detecting intracardiac thrombosis in adult Fontan patients. (1st December 2016) - Takeuchi, Daiji; Inai, Kei; Shinohara, Tokuko; Nakanishi, Toshio; Park, In-Sam
Abstract: Background: Coagulation abnormality is associated with a high incidence of intracardiac thrombus (ICT) and systemic thromboembolism in Fontan patients. The biomarker for detecting ICT is currently unknown. Methods: We retrospectively investigated the underlying coagulation abnormality and useful biomarkers to screen for ICT in adult Fontan patients. We measured various biomarkers of blood coagulation, fibrinolysis, and platelet activity in 122 Fontan patients (Fontan group: median age [P25–P75]: 27 [20–34] years) and compared them to those in 50 patients with atrial septal defect (ASD group: 31 [24–40] years). Results: Regardless of whether the patient had ICT, the Fontan group showed significantly lower levels of antithrombin III, thrombomodulin, and α2-antiplasmin; lower protein C and protein S activities; and significantly higher levels of thrombin-antithrombin complex and α2-plasmin inhibitor complex than the ASD group. Among various biomarkers, D-dimer level measured by using latex immunoassay was significantly higher in the patients with ICT (thrombus group: n = 21) than in the patients without ICT (non-thrombus group: n = 101). Fifteen (26%) of 57 patients on warfarin achieved prothrombin time international normalized ratios (PT-INRs) of > 2. The proportion of patients with PT-INRs of > 2 tended to be lower in the thrombus group than in the non-thrombus group (13% vs 31%). Persistent atrial arrhythmia and D-dimer level were significant risk factors associated with ICT formation in the multivariate analysis (persistent atrial arrhythmia: hazard ratio [HR], 6.89; 95% confidence interval [CI], 1.44–34.5; D-dimer: HR, 0.29; 95% CI, 0.13–0.50). Receiver-operating characteristic curve analysis revealed that the appropriate cutoff D-dimer level for screening for ICT was 1.8 μg/mL (area under the curve, 0.94), with a negative predictive value of 95%. Conclusions: In the adult Fontan patients, blood coagulation abnormalities existed regardless of the absence of ICT. D-dimer level may be a useful biomarker for screening for ICT in adult Fontan patients.